The Impact of the Application of PSAK 72 on the Financial Performance of Property Companies - Atmoko, Alfriadi Dwi (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2023)
This study aims to analyze revenue recognition based on PSAK 72 and its impact on the financial performance of property companies listed on the Indonesia Stock Exchange in 2019. The sample companies are 18, but only five implemented PSAK 72 in 2019. The five companies jointly implemented PSAK 71 on January 1, 2020, thus causing retrospective adjustments in 2018 and 2019 in its retained earnings that will have an impact on the statement of financial position and company performance. The method in this research uses the descriptive qualitative method. The data analysis technique used analyzes the five steps of the revenue recognition procedure based on PSAK 72. The results of this study show differences in the application of revenue recognition based on PSAK 72 with the previous standard resulting in changes in the value of revenue originating from customer contracts. Seen in each company's CR value has decreased, and the DTA value has increased for the five companies. At NPM, two companies experienced a decline due to the implementation of PSAK 72. However, the NPM at three companies has actually experienced an increase.